2015
DOI: 10.1007/978-3-319-27048-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Technologies for Smart Workplaces: A Workplace Efficiency Solution for Office Design and Building Management from an Occupier’s Perspective

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…In more general terms, we show that our methodology allows the study the effects of ABW principles applied in offices. This work goes one step further than previous work on ABW [26] in analysing not only occupancy data but also contacts between participants and by showing the potential of technology in gathering contacts data in a challenging environment where a traditional observation modality would struggle. The comparative analysis with more traditional offices also helps the understanding of the behavioural characteristics emerging from the application of ABW's principles.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In more general terms, we show that our methodology allows the study the effects of ABW principles applied in offices. This work goes one step further than previous work on ABW [26] in analysing not only occupancy data but also contacts between participants and by showing the potential of technology in gathering contacts data in a challenging environment where a traditional observation modality would struggle. The comparative analysis with more traditional offices also helps the understanding of the behavioural characteristics emerging from the application of ABW's principles.…”
Section: Introductionmentioning
confidence: 85%
“…To the best of our knowledge, only one work used technology to study this kind of workplaces. Ianeva et al used RFID tags embedded into employees' badges to monitor occupancy of spaces [26]. The authors found that three kinds of areas (cafeteria, private booths and meeting rooms) were consistently under-occupied, revealing a mismatch between intended and current use of these areas.…”
Section: Mobile Sensing For Office Analyticsmentioning
confidence: 99%
“…A promising application of IoT technology is related to the measurement of office occupation rates and the evaluation of the occupants' real use of the workspace. RFID technology (radio frequency identification) and Bluetooth proximity sensing have been used to monitor employees' location and building occupancy rates of activity-based offices (Clark et al, 2018;Ianeva et al, 2015). Through RFID tags inserted into employees' badges, a study collected real-time data about the occupation of different workspaces (meeting rooms, bubbles, workspaces, etc.)…”
Section: Jcre 221mentioning
confidence: 99%
“…Corporate Real Estate Management (CREM) and office design are strategic resources for business development. Real estate decisions must consider aspects such as employees' wellbeing, productivity, innovation, workplace flexibility and design (Ianeva et al, 2015). As impending real estate costs weigh heavily on the operating business, it is essential to measure the value and utilization of office space (Ward, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The room usage information is not only applicable to develop advanced control strategies, but they have also been applied to check real usage with room booking systems [17], especially in office buildings in which the private space is frequently needed and having them blocked and unused results in unnecessary wastes [30]. In addition, the wastes are not only economic as Corporate Real Estate (CRE) decisions address challenges such as productivity, employees’ well-being, innovation and flexibility; for which pervasive technologies offer potential for increasing workplace efficiency on a long-term basis [31].…”
Section: Related Workmentioning
confidence: 99%